Učna klima ter njena povezanost s samopodobo dijakov Gimnazije Kranj - Jurič, Sabina (Socialna pedagogika (Ljubljana), 2011)
Classroom atmosphere define all the interactions in the classroom, which is determined with reciprocal relations, personal growth of students and systemic characteristics of the class, which is the important starting point for teachers work. Classroom clime is connected with students achievement, their cognitive growth, motivation and self esteem of the students (Maxwell & Chmielewski, 2008; Roskam & Nils, 2007). In our survey we focused in the relation between the existent and desired learning climate in the classrooms of the first and the second grades, the estimation difference of existent and desired learning climate between male and female students and the possible connection of students self esteem and the classroom climate. There were 197 students answering the two self questionnaire: Learning climate - students (Zabukovec, 1998) and Self esteem questionnaire (SPA) (Pečjak & Krajnc, 1998). We assumed that first grade students will estimate the existent classroom climate higher than second grades students, and that the estimates of female students will be higher than male estimates of existent classroom climate as well. We predicted strong connections between students self esteem and existent classroom climate. The results denied all hypotheses. The second grade students estimated the existent climate higher than the first grade pupils, there were no distinction between male and female students at the existent climate estimation. The female students have higher desired classroom climate. The important connection between self esteem and classroom climate showed only at students family self esteem.
Keywords: classroom climate; razredno vzdušje; samopodoba; self-concept; srednja šola; secondary school; dijaki; učna klima; socialna pedagogika